Efficacy and putative mode of action of native and commercial antagonistic yeasts against postharvest pear pathogens - Lutz, María Cecilia (2013)
The putative mechanisms of action involved in the biocontrol capacity of four yeast strains (Cryptoccocus albidus NPCC 1248, Pichia membranifaciens NPCC 1250, Cryptoccocus victoriae NPCC 1263 and NPCC 1259) against Penicillium expansum and Botrytis cinerea were studied in vitro and in situ assays. C. albidus YP commercial strain was also evaluated with comparative purposes. All yeast strains showed different mechanisms including: wound colonization, germination inhibition, biofilms formation, secretion of killer toxins, competition for nutrient and secretion of hydrolytic enzymes (protease, quitinase and glucanase activities). The relationship between strains (and their associated antagonist mechanisms) and the in situ antagonist activity was also evaluated and our results suggest that mechanisms such as hydrolytic enzymes production, the ability for wounds colonization, toxin killer production and germination inhibition are the most important for biocontrol activity. Multiple modes of action as documented in this study might explain why P. membranifaciens NPCC 1250 and C. victoriae NPCC 1263 provided excellent control of postharvest pears disease.